High precision inter-continental GPS network - Monico, João Francisco Galera (1995)
GPS relative positioning provides precision of the order of 1 part per million (ppm) within relatively short periods of time. Considering this level of precision, together with the fact that the cost of GPS receivers is continuing come down, it is now apparent that most of the future geodetic surveys will be performed by GPS, It is therefore important to establish geodetic control networks which are suitable for geodetic GPS activities. The Brazilian Institute of Geography and Statistics (IBGE), which is the National Geodetic Surveying organization in Brazil, has proposed a high accuracy Brazilian GPS network, which has characteristics of an Active Control System (ACS). Such a system provides the users with the capability to perform relative positioning using only one receiver. An investigation of the methodology, algorithms and analysis, related to the IBGE network, has been carried out during this research. An initial investigation to assess the level of accuracy which can be obtained by a static user of the IBGE network equipped with only one receiver and observing within different scenarios, has shown relative precision in the range of 0.2 to 0.1 ppm.